Boreal Summer Negative Correlation Relationship Between Interannual SST and Precipitation Anomalies in the Tropical and Subtropical Western North Pacific. Issue 6 (24th March 2022) - Xue, Wei; Sun, Xuguang; Yang, Xiu‐Qun
Abstract: Western North Pacific (WNP) is a key region for ENSO development and its effect on East Asian summer monsoon. Different from most other tropical oceanic areas, sea surface temperature (SST) and precipitation anomalies over the WNP are negatively correlated in boreal summer, indicating the ocean is mainly driven by the atmosphere rather than the opposite over there. Two interannual variability modes of such negative correlation relationship are revealed with SVD method, called tropical and subtropical WNP air‐sea coupled modes (WNP‐TCM and WNP‐STCM) in terms of their locations accordingly. Their core regions are both consistent with the near‐zero line of low‐level zonal wind, corresponding to the Northwest Pacific monsoon trough and the west ridge of WNP subtropical high, respectively. In WNP‐TCM, precipitation anomaly is caused by local vorticity anomaly, which is the result of Matsuno‐Gill response to SST anomalies with the reversed signs in central equatorial Pacific and eastern equatorial Indian Ocean. In WNP‐STCM, it is produced by local divergence anomaly, which is remotely forced by SST anomalies with the same signs in equatorial Pacific and Indian Ocean through anomalous Hadley circulation. SST anomalies in the two modes are both controlled by ocean thermal process, especially the solar radiation anomaly. The key factors determining such unique WNP air‐sea interaction are the weak latent heat flux and horizontal SST advection anomalies, which are both closely related to the near‐zero low‐level zonal wind. In addition, WNP‐TCM often happens in ENSO developing summer whereas WNP‐STCM usually appears in ENSO decaying summer. Plain Language Summary: In most tropical ocean regions, much more precipitation is usually corresponding to warmer sea surface temperature (SST), and vice versa. However, in boreal summer, the western North Pacific (WNP) is an exception, where SST‐precipitation correlation is significantly negative, indicating the atmosphere drives the ocean. This study finds that negative SST‐precipitation correlation relationship in the WNP does not occur as a whole, nevertheless, it demonstrates independent tropical and subtropical modes that often happen in ENSO developing summer and ENSO decaying summer, respectively. It is interesting to note that both core regions of the two modes coincide with the near‐zero line of low‐level zonal wind, which is essential for the unique WNP air‐sea interaction. Remotely forced by different patterns of SST anomalies from equatorial Pacific and Indian Ocean, precipitation anomaly in the tropical mode is caused by the local vorticity anomaly whereas in the subtropical mode, it is attributed to the local divergence anomaly. Under the similarly major control of solar radiation due to precipitation anomaly, it is because of the weak latent heat flux and horizontal SST advection anomalies related to near‐zero low‐level zonal wind that, ocean thermal process instead of dynamic process dominates the SST anomalies in the WNP. Key Points: Tropical and subtropical modes of boreal summer negative sea surface temperature (SST)‐precipitation correlation are identified in the western North Pacific Precipitation anomalies in tropical and subtropical modes are caused by remote sea surface temperature anomaly (SSTA) via vorticity and divergence anomalies respectively Near‐zero low‐level zonal wind determines the weak latent heat flux and SST advection anomalies as well as the passive role of SSTA